An update on the management of hepatitis C virus-infected patients with stage 4–5 chronic kidney disease while awaiting the revised KDIGO Guidelines. Issue 1 (22nd March 2016) - Pol, Stanislas; Jadoul, Michel; Vallet-Pichard, Anaïs
Abstract : The treatment of hepatitis C virus (HCV) infection has progressed markedly over the last 2 decades, with a dramatic acceleration the last 3 years. The combination of two or three direct-acting antiviral drugs (DAAs) targeting viral proteins [NS3/4A protease inhibitors, NS5B nucleos(t)idic and non-nucleos(t)idic polymerase inhibitors, NS5A replication complex inhibitors], with or without ribavirin but without interferon (interferon-free regimen), for 8–24 weeks, achieved high sustained virological response (>90%), whatever fibrosis stage, genotype and subtype, baseline viral load, prior therapeutic history of the patient (naïve or experienced) and pre-existing resistance-associated variants with a fair tolerance and reduced pill burden. International guidelines recommend to ideally treat all infected patients even if a prioritization of the most severe patients (extensive fibrosis or cirrhosis, symptomatic cryoglobulinaemic vasculitis…) appears to be the best cost-effective and urgent policy. Patients with stage 4–5 chronic kidney disease (CKD) have to be considered as priority patients. Updating of the Kidney Disease: Improving Global Outcomes recommendations is due to start soon, but awaiting their availability, we present here an overview of recent developments in the field.